Heterologous Expression of Membrane Proteins Methods and Protocols - Mus-Veteau, Isabelle; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2010)
Membrane proteins play a key role in numerous pathologies such as cancer, cystic fibrosis, epilepsy, hyperinsulinism, and Alzheimer’s disease, yet studies on these and other disorders are hampered by a lack of information about the proteins involved. In Heterologous Expression of Membrane Proteins: Methods and Protocols, expert researchers provide an overview of the different heterologous expression systems available to produce these proteins for structural analysis, helping us to understand how these proteins function, and additionally, how their functions can be modified through drug treatment. Chapters examine membrane protein solubilization, purification, and instability in solution, and investigate the strategies that helped to determine the structure of the first heterologously expressed mammalian membrane proteins. Composed in the highly successful Methods in Molecular Biology™ series format, each chapter contains a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls. Far-reaching and innovative, Heterologous Expression of Membrane Proteins: Methods and Protocols, is an essential guide for novice and experienced researchers alike, providing detailed methods for existing expression systems alongside cutting-edge strategies for future use in the field. .
Heterologous Expression of Membrane Proteins for Structural Analysis -- Production of Membrane Proteins in Escherichia coli and Lactococcus lactis -- Mammalian Membrane Receptors Expression as Inclusion Bodies in Escherichia coli -- Expression of Membrane Proteins at the Escherichia coli Membrane for Structural Studies -- Membrane Protein Expression in Lactococcus lactis -- Heterologous Expression of Human Membrane Receptors in the Yeast Saccharomyces cerevisiae -- Mammalian Membrane Protein Expression in Baculovirus-Infected Insect Cells -- Expression of Membrane Proteins in Drosophila Melanogaster S2 Cells: Production and Analysis of a EGFP-Fused G Protein-Coupled Receptor as a Model -- Membrane Protein Expression in the Eyes of Transgenic Flies -- Expression of Mammalian Membrane Proteins in Mammalian Cells Using Semliki Forest Virus Vectors -- Membrane Protein Expression in Cell-Free Systems -- Practical Considerations of Membrane Protein Instability during Purification and Crystallisation -- Membrane Protein Solubilization -- Amphipols and Fluorinated Surfactants: Two Alternatives to Detergents for Studying Membrane Proteins In vitro -- Heterologous Expression and Affinity Purification of Eukaryotic Membrane Proteins in View of Functional and Structural Studies: The Example of the Sarcoplasmic Reticulum Ca2+-ATPase.
Keywords: Proteins .; Biochemistry; Cell biology; Proteomics; Cell membranes .; Protein Science; Biochemistry, general; Cell Biology; Proteomics; Membrane Biology